2020
DOI: 10.7717/peerj.9792
|View full text |Cite
|
Sign up to set email alerts
|

Life history and habitat do not mediate temporal changes in body size due to climate warming in rodents

Abstract: Temporal changes in body size have been documented in a number of vertebrate species, with different contested drivers being suggested to explain these changes. Among these are climate warming, resource availability, competition, predation risk, human population density, island effects and others. Both life history traits (intrinsic factors such as lifespan and reproductive rate) and habitat (extrinsic factors such as vegetation type, latitude and elevation) are expected to mediate the existence of a significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 90 publications
0
15
0
Order By: Relevance
“…In another meta-analysis of 73 North American mammal species, McCain and King 30 found the largest mammals examined were 27 times more likely to respond to climate change compared to the smallest mammals. These previous studies are all limited in that they are meta-analyses (also see 71 ), vary in statistical approach, and do not leverage the dense intraspecific sampling we achieved here. Our work draws strength from the use of a single hierarchical modeling framework for separate measures of body mass and head-body length and reveals a robust signal of larger mammals being more sensitive to variation in temperature, and conforming to Bergmann’s Rule.…”
Section: Discussionmentioning
confidence: 99%
“…In another meta-analysis of 73 North American mammal species, McCain and King 30 found the largest mammals examined were 27 times more likely to respond to climate change compared to the smallest mammals. These previous studies are all limited in that they are meta-analyses (also see 71 ), vary in statistical approach, and do not leverage the dense intraspecific sampling we achieved here. Our work draws strength from the use of a single hierarchical modeling framework for separate measures of body mass and head-body length and reveals a robust signal of larger mammals being more sensitive to variation in temperature, and conforming to Bergmann’s Rule.…”
Section: Discussionmentioning
confidence: 99%
“…This outcome adds to the very mixed picture of the change in body size in mammals under global climate change. The analysis of 50 species of rodents from seven families revealed no significant temporal change in body size (represented mainly by skull dimensions) in 29 species, a significant decline in 13, and an increase in size in eight species (Nengovhela et al 2020). Of the three carnivore species in which skull size was measured in the second half of the 20th century and analysed in the context of climate change, skull size showed a significant increase in two species and a significant decline in the other (Yom-Tov et al 2008, 2010a, 2010b.…”
Section: Discussionmentioning
confidence: 92%
“…Although the majority of studies did not find significant temporal changes in the sizes of birds and mammals, there are many examples of long-term body size and body mass changes (recorded over one to several decades) correlated with global climate change. While a decrease in size is indeed the major response in birds, the situation is much less clear in mammals, where many species increase in size (Teplitsky and Millien 2014;Naya et al 2017;Nengovhela et al 2020). This increase in size is usually explained as a reaction to increased food availability as a result of increasing temperatures (Yom-Tov and Geffen 2011; Boutin and Lane 2014 and references cited therein).…”
Section: Introductionmentioning
confidence: 99%
“…In another metaanalysis of 73 North American mammal species, McCain & King (2014) found that the largest mammals examined were 27 times more likely to respond to climate change compared to the smallest mammals. These previous studies are all limited in that they are meta-analyses (also see Nengovhela et al 2020), vary in statistical approach, and do not leverage the dense intraspecific sampling we achieved here. Our work draws strength from the use of a single hierarchical modeling framework for separate measures of body mass and head-body length and reveals a robust signal of larger mammals being more sensitive to changes in temperature, and conforming to Bergmann's Rule.…”
Section: Discussionmentioning
confidence: 99%